Undernutrition and Associated Factors among Under-Five Orphan Children in Addis Ababa, Ethiopia, 2020: A Cross-Sectional Study - Selam Shegaw Sewnet; Hunegnaw Almaw Derseh; Hanna Demelash Desyibelew; Netsanet Fentahun (Journal of Nutrition and Metabolism)
Background. Undernutrition contributes to the death of around 3 million children and threatens the futures of hundreds of millions, undermining healthy development and the strength of their societies by preventing children from achieving their full potential. Orphans are at greater risk of undernutrition because they are more likely to be extremely poor and receive less medical and social care. However, there is little information about the prevalence of undernutrition and associated factors among under-five orphan children. Objective. This study aimed to assess undernutrition and associated factors among under-five orphan children in orphanages in Addis Ababa, Ethiopia. Methods. An institution-based cross-sectional study was conducted in Addis Ababa from February 28 to March 28, 2020. A simple random sampling technique was employed to recruit a total of 275 orphan children. An interviewer-administered questionnaire and anthropometric measurements were used to collect data. Data were entered using EpiData version 3.1 and analysis was done by WHO Anthro version 3.2.2 and SPSS version 23. Multivariable logistic regression analysis was performed to identify determinants of undernutrition at a p value of less than 0.05 with an adjusted odds ratio of 95% confidence interval. Results. The prevalence of wasting, stunting, and underweight were 11.1%, 45.8%, and 25.5%, respectively. Presence of illness (AOR = 2.23; 95% CI: 1.41, 12.73), children who received less than three meals per day (AOR = 2.11; 95% CI: 1.58, 7.71), and children who were not vaccinated (AOR = 2.86; 95% CI: 2.07, 11.61) were significantly associated with stunting. Children who were not vaccinated (AOR = 2.04; 95% CI: 1.29, 9.71) and who had inadequate dietary diversity scores (AOR = 1.32, 95% CI: 1.16, 12.65) were significantly associated with wasting and underweight, respectively. Conclusion. The prevalence of undernutrition was very high compared to national data. Health status, meal frequency, and vaccination status were associated factors of stunting. Vaccination status and dietary diversity score were associated factors with wasting and underweight, respectively. Therefore, improving meal frequency, dietary diversity, and early treatment during childhood illness are important to reduce orphan undernutrition.